ALBANIAN OPHIOLITES. II - MODEL OF SUBDUCTION ZONE INFANCY AT A MID-OCEAN RIDGE - Insergueix-Filippi, Delphine; Dupeyrat, Laure; Dimo-Lahitte, Ardiana; Vergély, Pierre; Bébien, Jean (Ofioliti, 2000)
In the Albanian ophiolites, as well as in many other ophiolite complexes, tectonic, magmatic and geochronological evidences support the view that the intra- oceanic detachment preceding obduction is virtually contemporaneous with the oceanic accretion. Subduction zone infancy at a ridge axis has been numerically investigated by 2D thermal modelling of a convective upper mantle, with surface and subducting plates displacements prescribed by time-dependent kinematic conditions and with particular attention paid to the subducting oceanic lithosphere and the overlying mantle wedge. To explore the possible evolution of MORB, IAT, and boninitic magmatism with subduction progression, we overlaid reasonable chemical characteristics onto the thermal structures.Our experiments indicate that the initiation of a subduction at a ridge axis does not immediately stops the ascending asthenospheric flow, but leads to a deviation of its upper part in the same direction as the subducting lithosphere. Preservation of high temperatures in the mantle wedge explains the presence of short-lived boninitic magmatism at the earliest stages of subduction initiation which is partly contemporaneous with the progressive extinction of MORB magmatism and the initiation of arc magmatism. At the same time, temperatures in the subducting oceanic crust lead to the development of high temperaturehigh pressure metamorphic rocks. Despite of its relative simplicity, this numerical model accounts well for observations in supra-subduction zone ophiolites.